2021
DOI: 10.3390/biomedicines10010081
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Prevalence and Impact of Pulmonary Bacterial Colonisation in Stable State Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Background: Half of acute exacerbations of COPD are due to bacterial infection, and the other half are likely influenced by microbial colonisation. The same organisms commonly cultured during acute exacerbations are often found in the sputum of patients during stability. A robust assessment of the prevalence of potentially pathogenic microorganisms (PPMs) in the sputum of stable COPD patients may help to inform the targeted prevention of exacerbation by these organisms. Methods: A systematic review and meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Monitoring markers of oxidative stress and miR genotyping for precision-based chemotherapy [10] Iron-deficient COPD IV iron replacement Monitoring hepcidin as a marker for non-anaemic iron deficiency [23] Antimicrobial-resistant COPD Targeted antibiotics based on culture sensitivities Use of colour charts to determine commencement of antibiotics [14] Key-LABA: long-acting β-agonists; LAMA: long-acting muscarinic antagonists; ICS: inhaled corticosteroids; HRQoL: health-related quality of life; CFTR: cystic fibrosis transmembrane receptor; miR: microRNA; VTE: venous thromboembolism; NIV: noninvasive ventilation; OSA/ORRF: obstructive sleep apnoea/obesity-related respiratory failure; COPD: chronic obstructive pulmonary disease; IV: intravenous.…”
Section: Subgroup Established Treatment Future Management Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monitoring markers of oxidative stress and miR genotyping for precision-based chemotherapy [10] Iron-deficient COPD IV iron replacement Monitoring hepcidin as a marker for non-anaemic iron deficiency [23] Antimicrobial-resistant COPD Targeted antibiotics based on culture sensitivities Use of colour charts to determine commencement of antibiotics [14] Key-LABA: long-acting β-agonists; LAMA: long-acting muscarinic antagonists; ICS: inhaled corticosteroids; HRQoL: health-related quality of life; CFTR: cystic fibrosis transmembrane receptor; miR: microRNA; VTE: venous thromboembolism; NIV: noninvasive ventilation; OSA/ORRF: obstructive sleep apnoea/obesity-related respiratory failure; COPD: chronic obstructive pulmonary disease; IV: intravenous.…”
Section: Subgroup Established Treatment Future Management Considerationsmentioning
confidence: 99%
“…A systematic review by Armitage et al clarifies the prevalence of colonisation in stable-state COPD and identifies its relationship to the modality of sample collection [ 14 ]. The authors systematically identified 36 studies, which included a total of over 3000 patients, to perform a meta-analysis, identifying H. influenzae as the most prevalent PPM, colonising 41% of samples regardless of sampling method.…”
Section: Phenotype-guided Therapiesmentioning
confidence: 99%
“…The most commonly isolated microbes are H. influenzae, M. catarrhalis, S. pneumoniae, S. aureus, and P. aeruginosa . 3 …”
Section: Introductionmentioning
confidence: 99%
“…The most commonly isolated microbes are H. influenzae, M. catarrhalis, S. pneumoniae, S. aureus, and P. aeruginosa. 3 Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is an acute and sustained worsening of a patient's condition from a stable state. 4 Possible risk factors include air pollution, seasonal change, ethnic background, associated comorbidities, poor exercise capacity and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic bronchial infection is frequent in patients with moderate to severe COPD; up to 50% of patients may carry PPMs in their bronchial tree during stable state. 37 , 68 The persistence of PPMs in the lungs of patients with COPD may be defined as a CBI due to its impact on symptoms, exacerbations, and the natural history of the disease. 38 Due to its deleterious effects, CBI should be considered a treatable trait of COPD.…”
Section: Introductionmentioning
confidence: 99%